Impact of Poor Implementation of Welfare Policies on Training and Development on the Performance of Academic Staff in Selected Federal Universities in South-South Nigeria (International Journal of Scientific Research and Management (IJSRM), 2017)
The study on impact of poor implementation of welfare policies on training and development on the performance of academic staff in selected federal Universities in South-South Nigeria was carried out to examine the extent to which poor implementation of welfare policies on training and development impacts on the performance of workers in the selected Federal universities in South- South Nigeria. The equity theory was used to explain the variables. Interviews were conducted among 51 workers and the reports were analysed qualitatively. A total of 400 copies of structured questionnaire were also distributed among the workers and retrieved with a 90.7% response rate which were analysed quantitatively. The study discovered that, whereas there are good welfare policy statements in the study area, the level of implementation of these policies were poor. Furthermore, over 90% of the respondents insisted that full implementation of welfare policies would have positive impact on workers’ performance to a very large extent. The results further indicated that there have been very few in-house and outside training programmes in the study area. A total of 87% of respondents agreed that poor level of implementation of welfare policies on training and development is a source of discouragement which have negatively affected academic performance of both teaching and non-teaching staff and have led to poor service delivery in our Universities. The study advocate for a full implementation of welfare policies on training and development of academic staff by both the Federal government and the Federal University Management by increase funding, regular monitoring of funds and programme implementation level to enhance the performance of the academic staff in the federal Universities in the South-South Nigeria and the Country at large.